Differentiated Approach To Teaching In Russian Language Lessons - Yulduz Narzullaeva (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
This article examines the differentiated approach to teaching Russian language lessons as an effective pedagogical technology within the modern educational process. The study highlights the importance of competency-based education and the necessity of adapting instructional methods to students’ individual abilities, cognitive activity, and learning pace. Special attention is given to grouping learners according to their academic preparedness and psychological characteristics. The article analyzes the criteria for differentiation, describes the pedagogical tasks of the teacher for each group, and outlines practical methods used at different stages of the lesson. The findings demonstrate that differentiated instruction contributes to improving educational quality, fostering learner autonomy, and developing communicative competence.